PENGGUNAAN JARGON OLEH KOMUNITAS CHATTING FACEBOOK DI KALANGAN MAHASISWA UNIVERSITAS NEGERI PADANG - Vivi Kurnia; Ermanto Ermanto; Emidar Emidar (Jurnal Bahasa dan Sastra, 2013)
This article was written to describe the language, form, meaning, and function of the jargon used by the user community facebook chat with students Padang State University. The file of this study in the form of jargonfacebook chat user community among students Padang State University. The file source of this research is a conversation and dialogue among students and research as a communication interaction. File collected using the method and technique refer to note as advanced technique. The finding of the study first, jargon language used by the user community facebook chat among Padang State University students as seen from the use of language is considered the jargon Indonesian, English, and the Joint Indonesian and English. Second, the form it can be divided into abbreviations, acronyms, and phrases. Third, the meaning of jargon that is formed is not the true meaning of meaning connotations. Fourth, facebook chat user community using jargon that serves as a tool for communication in the familiar, sarcastic and streamline communication.